Effect of particle size of corn and sorghum grain on performance and digestibility for weaned pigs - S J Oh; G L Allee; Keith C Behnke; C W Deyoe (Kansas Agricultural Experiment Station Research Reports, 1983)
A 2 x 2 x 2 factorial experiment was conducted to evaluate the effects of two grain sources (corn or sorghum grain), two processing methods (hammer mill or roller mill), and two particle sizes (fine and coarse) on performance and nutrient digestibility of weaned pigs. Each grain was ground through a hammer mill with either a 1/8" (fine) or a 1/4" (coarse) screen. Average daily gain was not influenced by particle size, grain source or method of processing. Feed intake tended to increase as particle size increased, with the lowest feed intake on the fine particle size hammer-milled diet. Feed conversion improved as particle size decreased with both grain sources. Digestibilities of dry matter, nitrogen and energy improved as particle size decreased with both corn and sorghum grain.; Swine Day, Manhattan, KS, November 10, 1983
Keywords: Swine day; 1983; Kansas Agricultural Experiment Station contribution; no. 84-174-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 442; Swine; Particle size; Corn; Sorghum grain; Performance; Digestibility